2014
DOI: 10.1086/675539
|View full text |Cite
|
Sign up to set email alerts
|

Video Game Culture, Contentious Masculinities, and Reproducing Racialized Social Class Divisions in Middle School

Abstract: This short article examines how the mutual shaping of gender and technology can contribute to the reproduction of racialized class divisions. The article is based on an indepth ethnographic study of the launch of a progressive New York City public middle school. The school aimed to integrate twenty-first century digital technologies and skills into the curriculum as it promoted student-centered learning and social equity. The article argues that educators and privileged parents constructed an educational conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…From a sociological perspective, these divisions articulated two enduring axes of inequality: gender and racialized social class. All of the cliques were overwhelmingly organized around either a masculine or feminine orientation and, as such, they offered their participants different ways of doing masculinity and femininity (Sims, 2014). While some students occasionally perforated the gendered boundaries of these groups, by and large students clustered in groups where all of the participants identified as either boys or girls.…”
Section: Sanctioned and Unsanctioned Counterpracticesmentioning
confidence: 99%
“…From a sociological perspective, these divisions articulated two enduring axes of inequality: gender and racialized social class. All of the cliques were overwhelmingly organized around either a masculine or feminine orientation and, as such, they offered their participants different ways of doing masculinity and femininity (Sims, 2014). While some students occasionally perforated the gendered boundaries of these groups, by and large students clustered in groups where all of the participants identified as either boys or girls.…”
Section: Sanctioned and Unsanctioned Counterpracticesmentioning
confidence: 99%
“…Research on socioeconomic class outside of game form, however, is more common. Previous work done on players from different socioeconomic classes has primarily focused on youth of differing socioeconomic status, finding that class influences make a difference in how and what individuals play (Andrews, 2008;Sims, 2014). Demonstrating how race is implicated in class contexts, DiSalvo and colleagues found that both access to computers (to play educational games), as well as game content itself, can be an issue, such that "the lack of characters of color and the general themes have little crossover or relevance for them or their community" (DiSalvo et al, 2008: 138).…”
Section: Notesmentioning
confidence: 99%
“…The internet has helped shift transgender community experiences from "a pathologized transsexual population that existed around support and informational groups to a politicized transgender community that challenges society's gender paradigms" (Shapiro, 2004, p. 166). Building on feminist frameworks of sociotechnical interactions, I approach transvlogs as a source, consequence, and tool of gender and sociocultural relations (Sims, 2014).…”
Section: Transvlogsmentioning
confidence: 99%